PENGARUH PEMBERIAN VITAMIN E TERHADAP KADAR MALONDIALDEHID (MDA) PELARI JARAK JAUH SUMATERA BARAT - Meilisa Novya Wardani; Bafirman Bafirman; Pudia M Indika (JURNAL STAMINA, 2018)
Physical exercise weight. These things can cause muscle damage and decreased immunity. Vitamin E as an antioxidant that can minimize free radical free (MDA). Objective: From this study to determine the content of vitamin E to levels of Malondialdehid (MDA).This type of research is a pseudo experiment, with the research topic of all male athletes long distance runners of West Sumatra. Sampling technique is total sampling with 10 samples, sample data can be processed as many as 10 people. Provision of vitamin in the form of capsules with a dose of 400 IU consumed after 1-2 hours of exercise. The instrument in this research is the examination of the content of Malondialdehid using laboratory media (spectrophotometer), by Placer method.To know the level of Malondialdehyde nonparametric test (different test) The results showed that vitamin E to the level of Malondialdehid obtained Asymp Significance of 0.028 with a probability of 0.05. because 0.05> 0.028 then Haimaan (Hypothesis accepted / no influence). From the data test results can be found vitamin E content to levels of Malondialdehid (MDA) long distance runner West Sumatra.